Investigatory Study of the Growing Effect of African Teak (Pterocarpus erinaceus) Bark in Modified Feed Using Rabbit - Onyema, Agu Matthew; Garba, Suleiman Ismail; Yakubu, Shedrach; Inya, Agha Inya; Sylvester, Onyima Chibuike (Asian Journal of Environmental Research, 2024)
A total number of 3 growing rabbits about two weeks old were used in an experiment that lasted for 2 weeks. To investigate the growing effect of Pterocarpus erinaceus on growing rabbits. Three experimental diets, T1, T2, and T3 containing 0 %, 2.5 and 5 % of Pterocarpus erinaceus meal respectively were formulated, and three rabbits were randomly assigned to each diet. Daily feed intake was significantly higher in animals receiving Pterocarpus erinaceus bark meal than in animals on the control diet. Body weight changes of the animals on T1 were significantly higher than those on T2 and T3. The feed conversion ratio was the same in both T1, T2 and T3. The result of this experiment reveals that Pterocarpus erinaceus bark meal can be used in the diet for growing rabbits at a 5 % dietary level to enhance feed intake and weight gain thereby growing rabbits without compromising feed efficiency. The insight from the medicinal point of view makes the feed potent for ailment treatment and enhances both PCV and Hb. The initial PCV before the administration of the feed was for T1; 20.30 %, T2; 20.70 %, and T3; 21.68 %. After the administration of the feed, the final PCV was for T1; 24.60 % T2; 27.20 %, and T3; 28.20%. In the case of Hb, the initial Hb for T1 was 6.8, T2 was 6.9 and T3 was 7.2 whereas, after the administration of the feed, the final Hb for T1 was 8.2 g/dL, T2 was 9.2 g/dL and T3 was 9.4 g/dL. The use of Pterocarpus erinaceus as a natural source in meal preparation may help to reduce cost of feed preparation, improve, maintain and supplement to meet daily requirements of essential nutrients by reducing the use of synthetic food supplements.